Social Capital, R&D and Industrial Districts - Massimiliano Mazzanti; Giulio Cainelli; Susanna Mancinelli (Fondazione Eni Enrico Mattei (FEEM), 2005)
The main idea behind this paper is that social capital is not, as generally suggested by the socio-economic literature, an individual attitude towards something which does not imply privately appropriable economic benefits. Actually, SC might and should be interpreted as a public component of an investment which implies private and public benefits entangled with each other. In order to put forward this idea, a dynamic theoretical model that assumes social capital as the public component of the impure public good R&D is developed. It shows that the civic culture of the district area in which the firm works is not sufficient as an incentive to increase its investment in social capital, because this investment strictly depends on the economic convenience of investing in the impure public good. Social capital /networking dynamics might positively and complementarily evolve only if the opportunity cost of investing in innovation is sufficiently low. We consequently focus our attention on a specialized industrial district located in the Emilia Romagna region the biomedical district of Mirandola (Modena) characterised by a strong pattern of innovative activity. Using a proxy for innovative activity as dependant variable, we observe that R&D and networking/social capital arise as complementary driving forces for innovation outputs. When empirical evidence confirms that this complementarity plays a key role, and consequently strong links exist between market and non-market dynamics relating to firms, the role for policy actions targeted to social capital is larger. The policy effort should be targeted toward both market and non-market characteristics taken together, rather than solely to the production of (local) public goods (social capital) or innovation inputs as independent elements of firm processes. The input of SC alone is not sufficient to ensure innovation and growth: economic incentives matter. On the other hand, whenever SC dynamics are crucial for R&D private investments, the effect of economic incentives depends on the presence and degree of their complementarity.
Keywords: O32; D92; H49; 330; Social capital; R&D; Technological innovation; Industrial districts